1999
DOI: 10.1111/j.1600-0633.1999.tb00069.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and population genetic structure of river‐ and sea‐type sockeye salmon in western North America

Abstract: Abstract– In contrast to the well‐known "lake‐type" sockeye salmon, two additional anadromous life‐history types have been recognized within the species: ‘river‐type’ sockeye salmon whose juveniles spend 1 or 2 years in off‐channel river habitats prior to migrating to sea, and “sea‐type” sockeye salmon that initially rear in similar river habitats yet migrate to sea as underyearlings. Persistent populations of river‐/sea‐type sockeye salmon occur in small numbers throughout the species’range in North America b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 19 publications
2
44
2
Order By: Relevance
“…Extant populations of the sea/river ecotype exhibit sufficient genetic diversity to have founded populations of the other ecotypes by parallel evolution within regions. Gene diversity is typically as high or higher in sea/river‐type sockeye than in lake‐type sockeye based on allozymes (Wood 1995; Gustafson and Winans 1999), microsatellite DNA (Beacham et al. 2004, 2006) and mtDNA (this study).…”
Section: Discussionmentioning
confidence: 87%
“…Extant populations of the sea/river ecotype exhibit sufficient genetic diversity to have founded populations of the other ecotypes by parallel evolution within regions. Gene diversity is typically as high or higher in sea/river‐type sockeye than in lake‐type sockeye based on allozymes (Wood 1995; Gustafson and Winans 1999), microsatellite DNA (Beacham et al. 2004, 2006) and mtDNA (this study).…”
Section: Discussionmentioning
confidence: 87%
“…Although few studies have directly examined gene flow and river stability, Hendry et al (2004) review some studies that are consistent with the hypothesis. Gustafson and Winans (1999) showed that genetic differentiation was higher (gene flow lower) among lake-type sockeye from stable lake tributaries compared to river-type sockeye from river systems that do not have a lake to buffer flooding events. L'Abáe- Lund and Vøllestad (1985) suggest that gene flow may be higher among some freshwater species spawning in spring compared to fall because general stream conditions are more variable in spring (but see Quinn and Tallman 1987).…”
Section: Habitat Features and Population Divergencementioning
confidence: 97%
“…Chinook salmon vary in duration of marine residence, with 2-4 years being typical (Roni and Quinn, 1995). In sockeye salmon, the ''classic'' juvenile life history pattern involves one or two years of lake residence immediately after emergence from the gravel (Burgner, 1991) but some juveniles reside for a year in rivers if no lake is available (river-type) or migrate to sea in their first year of life (''sea-type'', reviewed by Wood, 1995, see also Gustafson and Winans, 1999). Birtwell et al (1987) reported that underyearling sockeye were very abundant in the Fraser River estuary, growing rapidly to 65-75 mm before leaving in early fall.…”
Section: Duration Of Stay In the Sea And In Fresh Watermentioning
confidence: 98%